Experimental Design in Constructing Low Temperature Sensor Based on Resistance Temperature Detector (RTD) - Suwito Singgih; Moh Toifur; Suryandari Suryandari (Indonesian Journal of Science and Education (IJOSE), 2020)
Thin film copper-based RTD still has a low TCR. Hence, plating a Cu-based RTD with nickel will develop a higher TCR. TCR is the sensitivity of RTD’s value in response to temperature change. The experimental design in constructing Cu/Ni thin film by using the electroplating method with a concentration of solution and electrode spacing’s variation has been done. Electroplating is performed with a concentration of solution and electrode spacing’s variations. Electroplating processed by limiting DC voltage to 6 volts. Electrolyte solutions composition were NiSO4, Ni2Cl2, H3BO3 and aquades. Concentrations of solutions can be varied by changing NiSO4 and Ni2Cl2 masses. Based on these concentrations of solutes and electrode’s spacing, this research used 15 samples. Thickness, thin-film resistance, and temperature sensor test are performed to each sample. The purpose of thickness test is to measure nickel plates which were formed from the electroplating process. Thin-film resistance test performed to measure sample resistance changing to the electroplating process, and the temperature sensor test was performed to measures the sample’s sensitivity in responding to temperature changes. This research’s result shows the greater the concentrations of solutes used for copper electroplating, the thicker nickel plates will form. This condition makes its resistance’s value decreasing.Keywords: thin layer resistance, concentration of the solution, electrode distance, electroplating, thin layers of Cu / Ni, RTD, modules